Participating in Physical Classes Using Eduball Stimulates Acquisition of Mathematical Knowledge and Skills by Primary School Students - Cichy, Ireneusz; Kaczmarczyk, Magdalena; Wawrzyniak, Sara; Kruszwicka, Agnieszka; Przybyla, Tomasz; Klichowski, Michal; Rokita, Andrzej (Frontiers in Psychology, 2020)
An increasing number of studies are evidencing relationships between physical activity and the mathematical performance of early school students. This is not surprising due to the fact that children grow in all areas simultaneously and their motor and intellectual development determine each other. Nevertheless, such an approach of combining mathematics education with physical exercises, in addition through play, which is the basis of children's activity and the preferred way of spending time, it is still rare at schools. In response to this problem "Eduball" has been created, which are educational balls with printed letters, numbers and other signs, used for team mini-games. Surprisingly, despite the studies on general usefulness of Eduball in preschool and early-school education and the effects of physical exercise classes carried out using these balls, still little is known about their impact on mathematical development. Here we investigate the relationships between the use of Eduball and the acquisition of mathematical knowledge and skills by children. We used a quantitative approach in the form of an experiment in natural settings in which seven-year-old students (first grade) took part (N=25). For the purposes of this experiment we created scenarios of physical exercise classes integrated with mathematical contents that used Eduball. Mathematical knowledge and skills were assessed by one of the commonly used tests. The results were compared with the data from the control group of traditional physical education classes (N=22). As assumed, after a one-year experiment students from both groups improved their results, but we found a greater progress in terms of mathematical knowledge and skills in the experimental class compared to the control one. Eduball particularly affected competences related to such mathematical categories as: sets and their elements, multiplication and division, geometric shapes and measuring length, measuring volume and mass. In sum, our results show that physical exercise classes that used Eduball stimulate the acquisition of mathematical competences by students, and, consequently, confirm that there is a strong relation of physical and mathematical development. Therefore, there is a need to review children's educational models, as well as primary school curricula, to combine physical and cognitive activities.